Cloud-Native Microservices for Real-Time Data Systems: A Technical Deep Dive - Sai Manish Podduturi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cloud-native microservices have emerged as a transformative solution for organizations facing the challenges of real-time data processing and analysis in today's digital landscape. This comprehensive article explores the fundamental components of cloud-native architectures, from their foundational principles to implementation best practices. The article examines how containerization, orchestration, and event-driven architectures enable unprecedented scalability and efficiency in handling modern data processing requirements. Through a detailed examination of microservices as building blocks, the research demonstrates how these architectural patterns significantly improve system reliability, performance, and maintainability. The article encompasses advanced monitoring and observability practices, highlighting their crucial role in maintaining robust cloud-native systems. By investigating real-world implementations across various industries, this study provides valuable insights into the practical benefits and challenges of adopting cloud-native approaches.
Keywords: Cloud-Native Architecture; Microservices Implementation; Container Orchestration; , Real-Time Data Processing; Event-Driven Architecture